2015
DOI: 10.4103/0976-237x.161857
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of innovative meloxicam mucoadhesive films for periodontal postsurgical pain control: A double-blinded, randomized clinical trial of effectiveness

Abstract: Background and Objective:Transmucosal analgesic delivery is a promising approach to periodontal postoperative pain management. The purpose of this clinical trial is to appraise the effectiveness of transmucosal drug delivery system with meloxicam films and to identify its minimum effective dosage via this route after periodontal flap surgery.Materials and Methods:The analgesic mucoadhesive films were formulated using meloxicam and hydroxypropyl methyl cellulose polymer by solvent casting method. The sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…These time intervals were selected based on the results of a study by Rajeswari et al ,[35] who evaluated periodontal postoperative pain control using meloxicam mucoadhesive films.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These time intervals were selected based on the results of a study by Rajeswari et al ,[35] who evaluated periodontal postoperative pain control using meloxicam mucoadhesive films.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study by Rajeswari et al ,[35] the power of the study was 80% and the required sample size was calculated as 13, which was rounded off to 15 patients with bilateral moderate or advanced periodontitis.…”
Section: Methodsmentioning
confidence: 99%
“…They performed a clinical trial on 68 patients and demonstrated a pain relief. Then, Al Hezaimi et al and Movassaghian et al published in 2010 and 2011, respectively, clinical trials showing pain relief using ketorolac and amitriptyline respectively compared to a placebo [6,17]. Throughout their investigations, these authors demonstrated that the formulation of their tablets, in term of molecular weight of the polymers and HPMC/CMC ratio, plays a crucial role.…”
Section: Literature Analysismentioning
confidence: 99%
“…However, on a clinical point of view, only a few of them have been evaluated. The main part of polymer used is composed of cellulose and its derivatives (cellulose, methylcellulose, carboxymethyl cellulose (CMC) and hydroxylpropyl methylcellulose HPMC)), which are formulated alone or with a copolymer [6,7,[13][14][15][16][17]. The formulations aim at optimizing the encapsulation of the analgesic while controlling its leakage.…”
Section: Delivery Devicementioning
confidence: 99%
See 1 more Smart Citation